The Effect of Green Tea (Camellia Sinensis) Infusion on Leydig Cell Count in Testis of Male Balb/C Mice Following Electronic Cigarette Exposure - Ni Luh Putu Ade Dinda Dewi Puspita (Journal of Social Research, 2026)
Exposure to electronic cigarette aerosol increases reactive oxygen species (ROS) production, leading to oxidative stress and potential damage to Leydig cells, which are crucial for testosterone synthesis. Green tea, particularly its polyphenol epigallocatechin gallate (EGCG), may protect testicular cells from oxidative damage. This study aimed to evaluate the effect of green tea (Camellia sinensis) infusion at two doses (0.03 g/mouse/day and 0.06 g/mouse/day) on Leydig cell count in male BALB/c mice exposed to electronic cigarette vapor. A randomized posttest-only control group design was used with 28 male BALB/c mice divided into four groups: negative control (KN), positive control with vitamin C (KP), treatment group 1 (P1: 0.03 g/mouse/day), and treatment group 2 (P2: 0.06 g/mouse/day). Mice were exposed to electronic cigarette vapor for 30 minutes daily over 30 days. Leydig cell counts were assessed with image raster analysis and HE staining. Data were analyzed using robust ANOVA and Tamhane’s post-hoc test. Significant differences were found among the groups (p = 0.000). P2 had the highest Leydig cell count (44.54 cells/field), followed by P1 (30.05 cells/field), KP (14.80 cells/field), and KN (13.40 cells/field). Significant differences were observed between KN–P1 (p = 0.004), KN–P2 (p = 0.008), KP–P1 (p = 0.006), and KP–P2 (p = 0.010), but no difference was found between P1–P2 (p = 0.251). Green tea infusion dose-dependently increases Leydig cell counts in exposed mice, outperforming vitamin C, though doses did not differ significantly.